Data from: Genomics reveals the role of admixture in the evolution of structure among sperm whale populations within the Mediterranean Sea - Violi, Biagio; de Jong, Menno; Frantzis, Alexandros; Alexiadou, Paraskevi; Tardy, Céline; Ody, Denis; De Stefanis, Renaud; Giménez Verdugo, Joan; Lucifora, Giuseppe; Silva, Mónica; Oliveira, Claudia; Alves, Filipe; et al. (Zenodo, 2023)
In oceanic ecosystems, the nature of barriers to gene flow, and the processes by which populations may become isolated are different from the terrestrial environment, and less well understood. In this study, we investigate a highly mobile species (the sperm whale, Physeter macrocephalus ) that is genetically differentiated between an open North Atlantic population and the populations in the Mediterranean Sea. We apply high-resolution single nucleotide polymorphisms (SNP) analysis to study the nature of barriers to gene flow in this system, comparing gene flow across the putative boundary into the Mediterranean (Strait of Gibraltar and Alboran Sea region) with novel analyses on structuring among sperm whale populations within the Mediterranean basin. Our data support a recent founding of the Mediterranean, around the time of the last glacial maximum, and shows concerted historical demographic profiles in both the Atlantic and the Mediterranean. In each region, there is evidence for a population decline around the time of the founder event, more extreme within the Mediterranean Sea where effective population size is substantially lower. While differentiation is strongest at the Atlantic/Mediterranean boundary, there is also significant differentiation between the Eastern and Western basins of the Mediterranean Sea. We propose, however, that the mechanisms are different. While post-founding gene flow was reduced between the Mediterranean and Atlantic populations, within the Mediterranean an important factor differentiating the basins is likely a greater degree of admixture between the Western basin and the North Atlantic. The two files, .ped and .map can be used within the R package SambaR (De Jong et al., 2021) in order to do S NP data management and analyses ( https://github.com/mennodejong1986/SambaR.git ). DATA FILTERING Once the dataset is imported, SNPs have to be filtered using the command filterdata(indmiss=0.5,snpmiss=0.05) to generate dataset A and filterdata(indmiss=0.25,snpmiss=0.05) for dataset B. ...